AIR POLLUTION ENGINEERING FOR ACCIDENTS WITH HAZARDOUS SUBSTANCES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
One of the challenges facing modern society is related to the dangers of industrial accidents and terrorist attacks related to the spread of fires and dangerous substances. In the present article, a systematic approach is proposed for organizing monitoring, creating possible development scenarios, modeling the spread of potential toxic-element pollution, comprehensive analysis and creating an adequate response to such severe situations. The assessment of the scale of pollution transport, dispersion, chemical transformation and the degree of danger is directly related to the correct registration of the basic accident, weather and environment characteristics and thoroughly monitoring of the dynamics of their change. The collection of the necessary data is carried out on the basis of heterogeneous sensor networks. The application of modern methods for the unification of disparate information scattered in space and time allows the accurate evaluation of the current state. Different development scenarios are generated on the basis of methodologies and corresponding mathematical models are applied. The risk assessment framework feeds these models with the unified sensor information and comprehensively examines them to provide a quantitative estimate of the possible critical levels of harmful pollution and predict the consequences. The paper's relevance is heightened by the growing threat of terrorism that targets industrial infrastructure and climate change that increase the frequency and severity of natural disasters, compounding the challenges of predicting and managing air pollution events. It contributes to the discourse on environmental engineering and disaster management by proposing a systematic methodology for real-time data collection, risk assessment, and the application of predictive models to inform effective response strategies. By tackling these issues, the paper aligns with contemporary priorities in environmental protection, public health, and safety regulations, making it highly topical for stakeholders in academia, industry, and government seeking to enhance resilience against air pollution disasters.;